POTENSI BRASSICA NAPUS SEBAGAI SUMBER BIODIESEL DI INDONESIA - Astarini, Ida Ayu (Bumi Lestari; Vol 13 No 1 (2013), 2013)
Abstract Seven Brassica napus cultivars were field tested to find out their adaptability and productivity in tropical dry land environment. The aim of this research is to identify potentially high oil yielding and agronomically stable Brassica napus genotypes as a new source of biodiesel in Indonesia. Crop evaluation includes germination rate, plant height, number of leaves and stomata, flowering time, harvesting time, seed yield and oil content. Oil extraction using ’cold pressing’ technique were trialed. Results show that all genotypes have good adaptability, therefore can be an alternative for biodiesel sources in Indonesia. Variation occurs on plant height, number of leaves, flowering time, seed set and oil content. ‘‘Tanami’’, ‘‘Trigold’’ and ‘‘Trilogy’’ has similar performance, short plants, high pod set and early flowering, while other cultivars have vigorous, tall plant habit but lower seed set. Some cultivars have an early flowering type while others has intermediate or late flowering. Pod set was excellence; however, seed set was low due to pest attack, namely Diamondback moth. Oil content of the seeds ranging from 2.6 to 11 %. In conclusion, B. napus are adaptable in dry land environment. Further study is needed to maximize seed production and oil content.
Keywords: Keywords: Brassica, biodiesel, adaptation, dry land